INTEGRATION OF CYBER COUNSELING AND MAQASID SYARIAH IN GUIDANCE AND COUNSELING SERVICES FOR GENERATION Z - Dewi Nadhipah; Alif Mu’arifah; Hardi Santosa (Universitas Islam Negeri Mataram, 2026)
The development of digital technology has encouraged guidance and counseling services to shift to cybercounseling, which is more accessible, flexible, and aligned with Generation Z's communication patterns. As digital natives, Generation Z faces various challenges, such as anxiety, social pressure, identity crises, cyberbullying, digital media dependency, and privacy vulnerabilities. However, studies on cyber counseling generally emphasize technical effectiveness and online communication, while the integration of spiritual values, ethics, dignity protection, and character building has not been systematically discussed. This study aims to develop a conceptual model for integrating cyber counseling and maqasid sharia in guidance and counseling services for Generation Z. The study used a qualitative approach with a systematic literature review design. Literature was collected from Google Scholar, Scopus, and accredited national journals between 2015 and 2024, selected according to the PRISMA principles, and analyzed using thematic analysis. The results show that maqasid sharia can serve as a normative framework to guide cyber counseling toward protecting life, mind, religion, lineage, and dignity. This integration results in a service model oriented towards mental health, digital literacy, strengthening spirituality, character building, online communication ethics, and protecting data confidentiality. The implication is that this model can help Islamic educational institutions provide safe, ethical, adaptive digital counseling services that support the well-being of Generation Z